2023
DOI: 10.3390/biomedicines11051302
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines as Diagnostic and Prognostic Markers for the Severity of COVID-19

Abstract: Accumulating evidence implicates obesity as a risk factor for increased severity of disease outcomes in patients infected with severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). Obesity is associated with adipose tissue dysfunction, which not only predisposes individuals to metabolic complications, but also substantially contributes to low-grade systemic inflammation, altered immune cell composition, and compromised immune function. This seems to impact the susceptibility and outcome of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 169 publications
1
8
0
Order By: Relevance
“…In agreement, Grewal and Buechler demonstrated that adipokines, mainly leptin, resistin and galectin-3, are closely involved in peripheral monocytes and neutrophil responses, which contributes to complications during the course of COVID-19 in patients with obesity. The authors also highlight that the overall inflammation in severe cases, as observed by routine markers, masks obesity-related inflammatory processes, which hampers treatment efficacy [ 10 ]. Therefore, despite comparable disease severity between COVID-19 groups, these observations indicate that patients with obesity have a distinct innate immunophenotype in severe COVID-19 that should be explored as biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement, Grewal and Buechler demonstrated that adipokines, mainly leptin, resistin and galectin-3, are closely involved in peripheral monocytes and neutrophil responses, which contributes to complications during the course of COVID-19 in patients with obesity. The authors also highlight that the overall inflammation in severe cases, as observed by routine markers, masks obesity-related inflammatory processes, which hampers treatment efficacy [ 10 ]. Therefore, despite comparable disease severity between COVID-19 groups, these observations indicate that patients with obesity have a distinct innate immunophenotype in severe COVID-19 that should be explored as biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…We also highlighted several surface receptors related to effector responses strongly and exclusively associated with clinical markers in patients with obesity. These phenotypes can help in monitoring in-hospital patients with obesity, since flow cytometry has become useful in clinical practice, for therapeutic decisions and vaccine development [ 10 , 53 , 55 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, adipokines may play a crucial role in pulmonary diseases, particularly in the context of inflammatory disorders, malignancies, and interstitial lung diseases. However, the associations between adipokines and interstitial lung disease (ILD) [ 4 ], asthma [ 5 ], chronic obstructive pulmonary disease (COPD) [ 6 ], lung cancer [ 7 ], tuberculosis [ 8 ], sleep apnea syndrome (SAS) [ 9 ], and pneumonia [ 10 ] remain unclear. Causality cannot be deduced from the existing evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations revealed new diagnostic biomarkers of the disease, such as mid-regional pro-adrenomedullin [2,3], monocyte distribution width [4,5], electrolyte imbalances [6], pentameric C-reactive protein [7], and pentraxin-3 [8,9]. Also, several recent studies provided insights on adipokines (chemerin, adiponectin, leptin, apelin, visfatin, resistin, galectin-3) as diagnostic and prognostic markers for the severity of COVID-19 [10,11]. Despite the vast volumes of existing evidence, several gaps exist in our understanding of COVID-19 biomarkers, and the pathophysiological basis on which these markers can foretell prognosis in COVID-19 remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%